Apuntes teóricos para un estudio macrosintáctico de la interrogación ecoica en el discurso digital - Aldama Pando, Isamary (Verba hispanica, 2025)
This study proposes a theoretical approach to the analysis of echo questions in digital discourse, a phenomenon that has received little attention in Hispanic linguistics. Its objective is to establish a conceptual and methodological foundation for describing the functions and discursive values of echo questions in computer-mediated communication. The research is grounded in Fuentes Rodríguez’s macrosyntactic analysis model (2017, 2019, 2024). A qualitative methodology was adopted, based on a critical review of the specialized li-terature and a preliminary analysis of a corpus of WhatsApp, Facebook, Instagram, and Twitter texts compiled in the MEsA corpus.
Keywords: digital discourse; digitalni diskurz; discursive relations; discurso digital; diskurzivna razmerja; echo questions; interrogación ecoica; macrosintaxis; macrosyntax; makroskladnja; odmevni vprašalni stavki; relaciones discursivas; sintaxis; skladnja; syntax